Innovation in X-Ray technology - Schulz,J. W. (2011)
In the Non-Destructive Testing (NDT) industry, the mayor trends are from film and stand alone applications to digital and inline inspection. Furthermore the quality requirements are growing driven by pushing design and material limits. Especially for field applications based on security reasons as well as image quality, replacement of isotopes can be monitored. With the move to digital the need for small focal spots at increased power requirements brought new challenges to the x-ray supplier. With the move to inline inspection systems, requirements for high uptime, fast throughput at the best possible resolution became the key challenges for the x-ray industry. The target to replace isotopes brings high challenges for weight size and energy. The innovation program of COMET delivers solutions for those challenges. Comparison between 600 Kilovolts (kV) and conventional 450kV x-ray sources will show the advantages in penetration and resolution and with this in defect recognition. The resolution gain with adaptive focal spots compared to standard focal spots will be presented and the advantages of maintenance reduced high voltage cables will be shown.